To accept or not to accept a job offer: Examining inaction inertia in an organizational context. Issue 11 (24th August 2017) - Foster, Christina C.; Diab, Dalia L.
Abstract: The purpose of this research was to investigate inaction inertia in a job offer context. Across two studies, we examined the influence of two situational factors (Study 1) and one dispositional factor (Study 2) on inaction inertia in a job offer context. Participants were asked to imagine they had to pass up an initial offer in which they were interested, but that they received a similar but less attractive offer (lower salary) later. Study 1 findings revealed participants in the loss‐framed condition were more likely to accept the second offer than participants in the neutral condition only when they were asked to imagine they were switching careers, versus being laid off. Study 2 results showed that maximizing tendency significantly and negatively predicted the likelihood to accept the second job offer. Exploratory analyses revealed that anticipated regret did not mediate the relationships between any of the factors and inaction inertia, suggesting that anticipated regret was not the causal mechanism underlying the occurrence of inaction inertia in the current research. Overall, this research shed light on the ways inaction inertia may be experienced in a job offer context.